2020
DOI: 10.1177/0896860820923238
|View full text |Cite
|
Sign up to set email alerts
|

Salvage of the peritoneal dialysis catheter in Candida peritonitis using amphotericin B catheter lock

Abstract: Candida species form biofilms, facilitating adherence to peritoneal dialysis (PD) catheters and making them less susceptible to antifungal therapy. Therefore, the International Society for Peritoneal Dialysis recommends immediate PD catheter removal in case of Candida peritonitis. However, in 2007, our institution showed that Candida peritonitis could be successfully treated without catheter removal with a treatment strategy including amphotericin B as catheter lock. To confirm the efficacy and safety of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Examples are temporary discontinuation of PD without removing the catheter (peritoneal rest) combined with intravenous meropenem and meropenem intracatheter as lock (Mero-PerRest protocol) in case of enteric peritonitis and the treatment with amphotericin B catheter lock for salvage of the PD catheter in case of Candida peritonitis. 32,33…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples are temporary discontinuation of PD without removing the catheter (peritoneal rest) combined with intravenous meropenem and meropenem intracatheter as lock (Mero-PerRest protocol) in case of enteric peritonitis and the treatment with amphotericin B catheter lock for salvage of the PD catheter in case of Candida peritonitis. 32,33…”
Section: Discussionmentioning
confidence: 99%
“…Examples are temporary discontinuation of PD without removing the catheter (peritoneal rest) combined with intravenous meropenem and meropenem intracatheter as lock (Mero-PerRest protocol) in case of enteric peritonitis and the treatment with amphotericin B catheter lock for salvage of the PD catheter in case of Candida peritonitis. 32,33 Catheter-related problems have been identified as an important cause of early technique failure in previous studies. 10,23 In this study, we identified leakage as another important cause of early technique failure.…”
Section: Discussionmentioning
confidence: 99%